2011
DOI: 10.3389/fncel.2011.00010
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Dendrodendritic Inhibition in the Mammalian Olfactory Bulb

Abstract: The mitral–granule cell (MC–GC) reciprocal synapse is an important source of auto- and lateral-inhibition in the olfactory bulb (OB), and this local inhibition is critical for odor discrimination. We may gain insight into the role of MC autoinhibition in olfaction by correlating the functional development of the autoinhibition with the postnatal development of olfactory function. We have studied the functional development of the MC–GC reciprocal synapse using whole-cell patch-clamp recordings from MCs and GCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 80 publications
4
19
0
Order By: Relevance
“…First, we observed a strongly reduced release probability P r (0.1 vs. 0.5). This effect might be due to maturation of the bulbar network, since in rats the strength of dendrodendritic inhibition was reported to decline steeply between PND15 and PND20 (Dietz et al, 2011). While this P r value is no more than an estimate due to the small number of recorded responses and substantial noise in some experiments, we observed similar values also for recordings from ∆GluN1 and ∆GluA2 GCs, with the slight increase for ∆GluA2 possibly explained by the improved detectability of signals in these cells.…”
Section: Postsynaptic Ca 2+ Signals In Adult Mouse Versus Juvenile Ratsupporting
confidence: 69%
“…First, we observed a strongly reduced release probability P r (0.1 vs. 0.5). This effect might be due to maturation of the bulbar network, since in rats the strength of dendrodendritic inhibition was reported to decline steeply between PND15 and PND20 (Dietz et al, 2011). While this P r value is no more than an estimate due to the small number of recorded responses and substantial noise in some experiments, we observed similar values also for recordings from ∆GluN1 and ∆GluA2 GCs, with the slight increase for ∆GluA2 possibly explained by the improved detectability of signals in these cells.…”
Section: Postsynaptic Ca 2+ Signals In Adult Mouse Versus Juvenile Ratsupporting
confidence: 69%
“…Similarly, even though we found that bidirectional plasticity was most likely not specific to a given cell, bidirectional plasticity might be due to differing maturational stages of GCs and their synapses, since the early development of the olfactory bulb network is not yet terminated in two-week old animals (e.g., [ 61 ]). While the GCs in our sample appeared mature with respect to their anatomy and action potential firing [ 62 ], more subtle gradations of maturation could affect plasticity.…”
Section: Discussionmentioning
confidence: 95%
“…Ca 2+ -spike generation was facilitated by close packing of spines that were located on the same and/or a rather low number of branches (Fig 8C and 8E). Finally, developmental effects might influence synaptic density and excitability in early born granule cells within the age range used here [37,38]; however, there were no correlations between threshold spine numbers and animal age (Fig 8F).…”
Section: Limited Influence Of Morphology On Nonlocal Spike Generationmentioning
confidence: 91%